2005
DOI: 10.1590/s1413-78522005000500004
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude de movimento após artroplastia total do joelho

Abstract: OBJETIVO: Avaliar a amplitude de movimentos (ADM) do joelho após seis meses de pós-operatório de artroplastia total, comparando-a com o seu valor pré-operatório. MATERIAL E MÉTODOS: Foi analisada a amplitude de movimento de 80 artroplastias, com acompanhamento pós-operatório médio de 21,9 meses. RESULTADO: Não houve diferença significativa entre as médias pré e pós-operatória, de extensão (p=0,09) e flexão (p=0,47). Subdividindo os pacientes em dois grupos, naqueles com flexão pré-operatória menor ou igual a 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
1
5
0
6
Order By: Relevance
“…The mean arc of motion (104.7°) observed in our study is considered satisfactory and is similar to results found in the literature, such as a study by Carvalho Júnior et al, 28 in which the reported mean of postoperative flexion arc was 108.6°.…”
Section: Discussionsupporting
confidence: 91%
“…The mean arc of motion (104.7°) observed in our study is considered satisfactory and is similar to results found in the literature, such as a study by Carvalho Júnior et al, 28 in which the reported mean of postoperative flexion arc was 108.6°.…”
Section: Discussionsupporting
confidence: 91%
“…Several factors may influence the post-TKA ROM, including pre- and perioperative ROM, surgical technique, posterior cruciate ligament (PCL) resection, prosthesis design, and postoperative rehabilitation 8, 9, 10, 11. In some groups and in certain situations, even ROM loss has been described after TKA 9, 11, 12, 13, 14. Some studies also discuss the importance of the perioperative ROM as an indicator of the final movement; to the best of the authors’ knowledge, there are no studies using medial pivot prostheses 12, 13, 15…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho Júnior et al 6 tiveram como objetivo do trabalho avaliar a amplitude de movimentos (ADM) do joelho após seis meses de pós-operatório de artroplastia total, comparando-a com o seu valor pré-operatório. Foi analisada a amplitude de movimento de 80 artroplastias, com acompanhamento pós-operatório médio de 21,9 meses.…”
Section: Discussionunclassified